New Chimeric Antigen Receptor Design for Solid Tumors - Wang, Yuedi; Luo, Feifei; Yang, Jiao; Zhao, Chujun; Chu, Yiwei (Frontiers in Immunology, 2017)
In recent years, chimeric antigen receptor (CAR) T-cell therapy has become popular in immunotherapy, particularly after its tremendous success in the treatment of lineage-restricted hematologic cancers. However, the application of CAR T-cell therapy for solid tumors has not reached its full potential because of the lack of specific tumor antigens and inhibitory factors in suppressive tumor microenvironment (TME) [e.g., programmed death ligand-1(PD-L1), myeloid-derived suppressor cells (MDSC), and transforming growth factor-β (TGF-β)]. In this review, we include some limitations in CAR design, such as tumor heterogeneity, indefinite spatial distance between CAR T-cell and its target cell, and suppressive TME. We also summarize some new approaches to overcome these hurdles, including targeting neoantigens and/or multiple antigens at once and depleting some inhibitory factors.